PROPRIEDADES DIELÉTRICAS DO Bi2Sn2O7 PURO E DOPADO COM MANGANÊS - Almeida, Rafael Mendonça (2010)
In this work we have investigated the dielectric and ionic properties of the pure Bi2Sn2O7 (BSO) and manganese doped ceramics in the temperature range from 23°C to 326°C. Amongst the main results of the BSO it is worthwhile to point out the PTCR ef-fect when it was analysed the temperature dependence of the electrical resistance. Furthermore, in both samples, the imaginary electrical modulus relaxational peaks are related to conductive processes, but only the BSO shows an anomaly in the tempera-ture range investigated. This anomaly is expressed with a displacement of the peaks to the region of low frequencies, as the temperature rises from the ambient value until 100°C, and after to the region of high frequencies, when the temperature changes from 100°C to 326°C. This dynamic of the data allowed to estimate the phase transition value as being equal to 121.5°C. It was also observed that this transition is possibly ferroic because the capacitance dependence with temperature shows a Curie like behaviour. By other side, the analysis of the real part of the electrical permittivity with temperature highlighted that the BSO phase transition point is located some-where around 125°C, while the one from BSO:Mn is around 120°C. The conductivity dependence with the reciprocal temperature showed an Arrhenius like behaviour and, from the mathematical adjustment at high temperatures, it was possible to estimate an activation energy of 1.26 eV. It was also found that the manganese doping inhibited the effect observed in the graphs of versus frequency, favored the conduction me-chanism of the system and preclude the PTCR effect. Analyzing the temperature de-pendence of the dielectric loss it was realized that this quantity also presents an ano-maly at around 120°C that can be assigned to the structural phase transition. Studying the real part of the admittance as function of the frequency, one could segregate the contributions from the bulk and grain boundary of the system and observe that the response of the last one exhibits a peak at 120°C, probably due to the transi-tion. Regarding the manganese ion substitution in the BSO structure, two hypotheses are proposed. It is believed that in both, the tin ion occurs with an oxidation state equal to 2+ and, but substituting either in the tin ion site or in the bismuth ion site, and releasing oxygen vacancies.